Designing intelligent healthcare organisations with KM and ICT. (16th May 2008) - Dwivedi, A.; Wickramasinghe, N.; Bali, R.K.; Naguib, R.N.G.
One of the fundamental challenges faced by the 21st Century clinical practitioner is to acquire proficiency in understanding and interpreting clinical information so as to attain knowledge and wisdom and then apply this through making prudent treatment decisions. We focus on the emergence of telehealth as an alternative implementation for transfer of medical information using futuristic ICTs. A Knowledge Management (KM) solution is proffered so as to allow knowledge derivation of voluminous and disparate data for more effective clinical diagnosis. We contend that integrating KM and ICT into healthcare organisational processes will lead to more effective and efficient healthcare operations.